Systematic Literature Review (SLR): Pengaruh Self-Directed Learning terhadap Kemampuan Koneksi Matematis Siswa pada Materi Fungsi Eksponensial - Desi Fitriani; Rhomiy Handican; Rilla Gina Gunawan (Griya Journal of Mathematics Education and Application, 2022)
Connection ability is one of the most important higher order thinking skills and must be developed because in learning mathematics every concept is related to one another. The learning model that is able to hone mathematical connection skills is self-directed learning (SDL). Individuals who have high self-directed learning are individuals who are proactive, have their own initiative, are resourceful, and are individuals who have a responsibility to always learn. This study aims to conduct a literature review related to the Self-Directed Learning model and the ability of mathematical connections. The research method used in this study is the SLR (Systematic Literature Review) method. Data collection is done by documenting all articles that have similar research in research reports. The articles used in this study were 15 national journal articles obtained from the Google Scholar database using the Harzing's Publish or Perish application. Based on this research, it was found that self-directed learning is an independent learning model that can motivate students in learning and can make a student continuously seek information in order to improve abilities. The learning model that is able to hone mathematical connection skills is Self-Directed Learning (SDL).